Building a Sakinah Family of Qur'anic Memorizers: A Strategic Approach and Dynamics in the Framework of Contemporary Islamic Family Law - Digdo Aji Mukti; Zamakhsyari bin Hasballah Thaib; Fahrozi; Muh Zaitun Ardi; M. Fijar Ishlahul Ummah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Purpose – This study examines the dynamics of al-Qur'an memorizing couples in Roudlatul Qur'an Islamic Boarding School in Metro City in building a sakinah family. This study aims to fill the gap in the literature regarding the influence of the practice of memorizing the Qur'an on family relationships and daily life in the context of contemporary Islamic family law. This study argues that the spiritual practice of memorizing the Qur'an can be a significant strategy in improving family harmony and emotional well-being, making it relevant to be used as a reference in a strategic approach to building a sakinah family in the modern era. Methods – This research utilized a phenomenological study to gain in-depth insight into the informants' experiences. Data were collected through semi-structured interviews with three couples who memorize the Qur'an and work as teachers at Roudlatul Qur'an Islamic Boarding School. The interviews were analyzed using thematic analysis to identify key themes and patterns relating to the impact of Qur'ānic memorization on contemporary family dynamics. Findings – This study reveals that the activity of memorizing the Qur'an contributes significantly to controlling emotions, creating inner calm, and increasing wisdom in family decision-making. Couples who engaged in this activity reported increased self-awareness as well as the ability to handle conflicts more calmly and wisely. These results support the view that listening to and memorizing the Qur'an not only reduces stress levels, but also promotes inner peace through mechanisms involving the release of natural endorphins and delta wave stimulation. These findings are relevant in the context of building a sakinah family in the environment of Pesantren Roudlatul Qur'an Metro City, particularly within the framework of contemporary Islamic family law. Research limitations – Some limitations of this study include the small sample size and focus on one particular location, which may affect the generalizability of the findings. Further research with a larger sample and various locations is needed to strengthen the conclusions. Originality – This study makes an important contribution to the literature on the role of spirituality in contemporary family dynamics. The results of this study show that Qur'an memorization not only has an impact on spiritual aspects, but also on emotional and psychological aspects, thus providing a strong foundation for achieving a sakinah family. This research also opens up opportunities for further research on how religious practices can be used to improve the quality of family life.